Strategi Pelaksanaan Evaluasi Program Pendidikan Terhadap Kualitas Belajar Siswa Di Sekolah - Fazli Abdillah; Khoirul Azmi; Casyariadi Vana Hafizah; Dea Anisha; Nurana Dwina Bintang; Sri Mulyani (Jurnal Bintang Pendidikan Indonesia, 2023)
Assessment that is often understood so far in the world of learning is limited to evaluation only. This evaluation was tried formatively and summatively. When an evaluation has been attempted, it is considered that the assessment has been carried out. Such a description is not very fitting. The application of evaluation tends to only look at the achievement of educational goals. In this case, in the learning process it is not only the value that is seen, but there are many aspects that make the success or failure of a program. Evaluation is only a small part of the assessment. Assessment must also be understood as part of supervision. Assessment does not only deal with values that are measured based on solving questions, but assessment of learning programs will examine many aspects. Implementation of learning programs can be viewed from various perspectives. This point of view includes the government as a policy maker, from citizens as users, from educators, for example in terms of program effectiveness. To determine the success of the learning program implemented, an assessment is needed, which is called program evaluation. Because it specifically evaluates learning programs, it is often referred to as evaluating learning programs. Assessment is used more as a strategy to measure how far the success of education is. Given the importance of this and also remembering that assessment is one of the benefits of learning management that cannot be ignored, this paper will discuss program evaluation in learning.